The Implementation of Building Setback Regulations along K.Z. Abidin I Road in Bengkulu City under Mayor Regulation Number 38 of 2018 - Muhammad Farhan; Muhammad Hafizh Aziz; Giska Wulandari; Desi Hafizah (The Future of Education Journal, 2026)
The rapid urban development in Bengkulu City has raised serious concerns regarding compliance with Building Setback Line (GSB) regulations, particularly along Jalan K.Z. Abidin I. This study aims to examine the implementation of GSB provisions based on Bengkulu Mayor Regulation Number 38 of 2018 concerning Road Classification and Fence Setback Line/Building Setback Line, as well as to analyze the efforts of the local government in enforcing these provisions. The research employs a normative juridical method with a statute approach and a conceptual approach, utilizing primary, secondary, and tertiary legal materials analyzed through qualitative descriptive-analytical techniques. The findings reveal that Jalan K.Z. Abidin I is classified as a Secondary Collector Road with a required GSP/GSB of 10/20 meters, yet numerous permanent structures continue to violate these standards, reflecting a significant gap between das sollen and das sein. The Bengkulu City Government through the Public Works and Spatial Planning Office (DPUPR) and the Civil Service Police Unit (Satpol PP) has undertaken preventive measures such as issuing regulations, implementing building permit mechanisms, and conducting public outreach, as well as repressive measures including field inspections, direct measurements, and the issuance of graduated warning letters. However, law enforcement has remained ineffective and inconsistent due to the lack of political will on the part of the local government, limited institutional capacity, low public legal awareness, and disparities in enforcement that contradict the principle of equality before the law.